Millennium BCP equity research one bank: 3 Worlds - Bereziy, Darya (2022)
This is one of two parts of an Equity Research on the Portuguese Bank Millennium BCP. In this part, an overview of the macro environments in Mozambique, Poland, and Portugal. Several impactful topics for each geography are overviewed. For Mozambique, the impact of, the insurgence, the natural gas megaproject, and the new monetary policy, is analyzed. For Poland, the populational growth, economy’s productivity and convergence towards different European countries is analyzed. Finally, for Portugal the possibility that inflation throws Europe in a new healthy growth phase is explored. The recovery from the pandemic is also explored for the 3 geographies. Additionally, forecasts for Net Interest Income Interest are explained, and also the evolution of the respective balance sheet items, the most significant being, loans, and deposits. Considering the procyclicality of the banking industry the macroeconomic environment is especially important. Taking all these scenarios and event into account a target share price is €0.2020 was obtained.